2017
DOI: 10.26493/1855-3974.1132.fae
|View full text |Cite
|
Sign up to set email alerts
|

Counting faces of graphical zonotopes

Abstract: It is a classical fact that the number of vertices of the graphical zonotope ZΓ is equal to the number of acyclic orientations of a graph Γ. We show that the f -polynomial of ZΓ is obtained as the principal specialization of the q-analog of the chromatic symmetric function of Γ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…The main argument in [12] of the proof of Theorem 4.4 for graphical zonotopes was based on the Humpert and Martin cancelation-free formula for the antipode of the chromatic Hopf algebra of graphs [14].…”
Section: Specializations Of the Enumerator F Q (Q)mentioning
confidence: 99%
See 3 more Smart Citations
“…The main argument in [12] of the proof of Theorem 4.4 for graphical zonotopes was based on the Humpert and Martin cancelation-free formula for the antipode of the chromatic Hopf algebra of graphs [14].…”
Section: Specializations Of the Enumerator F Q (Q)mentioning
confidence: 99%
“…On the other hand, when a class of generalized permutohedra is specified we obtain the well known combinatorial enumerators. The case of graphical zonotopes Q = Z Γ is studied in [12]. The quasisymmetric function F q (Z Γ ) is a q-refinement of the Stanley chromatic symmetric function X Γ of graphs…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 6.5. Grujić [18] has shown that the f -polynomial of Z G , which encodes the number of faces of Z G in each dimension, can be obtained as the principal specialization of the q-analogue of the chromatic symmetric function of G.…”
Section: Graphical and Laplacian Zonotopesmentioning
confidence: 99%